Prognostic impact of aetiology in adult hemophagocytic lymphohistiocytosis: insights from an intensive care unit experience - Rita Noversa de Sousa; Andreia Sá Lima; Susana Viana; Filipa Guimarães; Marta Pereira; Luís Miguel Afonso (European Journal of Case Reports in Internal Medicine)
Background: Hemophagocytic lymphohistiocytosis (HLH) is a rare, life-threatening hyperinflammatory syndrome marked by excessive immune activation. It can be triggered by various factors, including infections, malignancies, and autoimmune diseases, making the diagnosis challenging due to its overlap with other severe conditions. Case reports: We discuss two intensive care unit (ICU) cases illustrating the diverse manifestations of HLH and the critical importance of early recognition and treatment. The first case involves natural killer-cell leukaemia, and the second, a suspected viral trigger. Both highlight the necessity of a multidisciplinary approach in diagnosis and management, emphasizing the complexity of HLH in ICU settings. Conclusions: High mortality rates, particularly in malignancy-associated HLH, underscore the importance of tailored treatment strategies based on the underlying aetiology.